Environmental cadmium exposure and metabolic responses of the Nile tilapia, Oreochromis niloticus - Almeida, J. A.; Novelli, ELB; Silva, M. D.; Alves, R. (Elsevier B.V., 2001)
The contamination of water by metal compounds is a worldwide environmental problem. This study was undertaken to evaluate the impact of short-term cadmium exposure on metabolic patterns of the freshwater fish Oreochromis niloticus. The fish were exposed to 320, 640, 1280 and 2560 mug/l sublethal concentrations of Cd++ (CdCl2) in water for 7 days. The specific activities of the enzymes phosphofructo kinase (PFK-E.C.2.7.1.11.), lactate dehydrogenase (LDH-E.C.1.1.1.27.) and creatine kinase (CK-E.C.2.7.3.2.) were decreased in white muscle after cadmium treatments, indicating decreases in the capacity of glycolysis in this tissue. Cadmium exposure induced increased glucose concentration in white muscle of fish. on the other hand, cadmium exposure at sublethal concentrations increased phosphofructo kinase and LDH in red muscle of fish. Cadmium significantly decreased total protein concentrations in liver and white muscle regardless of tissue glycogen levels. The data suggest that cadmium acts as a stressor, leading to metabolic alterations similar to those observed in starvation. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: cadmium; contamination; fish; metabolic responses